Mythic Frontiers : Remembering, Forgetting, and Profiting with Cultural Heritage Tourism - Maher, Daniel R. (Cultural heritage studies., 2016)
The history of the Wild West has long been fictionalized in novels, films, and television shows. Catering to these popular representations, towns across America have created tourist sites connecting such tales with historical monuments. Yet these attractions stray from known histories in favor of the embellished past visitors expect to see and serve to craft a cultural memory that reinforces contemporary ideologies. In Mythic Frontiers, Daniel Maher illustrates how aggrandized versions of the past, especially those of the "American frontier," have been used to turn a profit. These imagined historical sites have effectively silenced the violent, oppressive, colonizing forces of manifest destiny and elevated principal architects of it to mythic heights. Examining the frontier complex in Fort Smith, Arkansas--where visitors are greeted at a restored brothel and the reconstructed courtroom and gallows of "Hanging Judge" Isaac Parker feature prominently--Maher warns that creating a popular tourist narrative and disconnecting cultural heritage tourism from history minimizes the devastating consequences of imperialism, racism, and sexism and relegitimizes the privilege bestowed upon white men.